Genetic Ranking of Potato Varieties is Different in Scandinavian and Mediterranean Environments - Muhammad Farhan Yousaf; Hélène Romé; Merethe Bagge; Mathias Timmermann; Just Jensen; Thinh Tuan Chu (American Journal of Potato Research, 2026)
Understanding genotype-by-environment interaction (G×E) is essential for breeding potato cultivars adapted to different regions. We analyzed ~ 13,000 tetraploid breeding lines evaluated over 17 years in Denmark (DK), Spain (ES), and Morocco (MO), representing Scandinavian and Mediterranean mega-environments. A pedigree-based mixed model was fitted for yield, tuber size, and resistance towards scab. Significant G×E was detected for yield and scab, evidenced by lack of unit genetic correlations between environments, heterogeneous genetic variances, and differing heritabilities. Additive genetic correlations for yield were 0.54 (DK–ES), 0.64 (DK–MO), and 0.78 (ES–MO); scab correlation between DK and ES&MO was 0.6. Yield genetic variance in ES was more than twice compared with DK and MO, whereas scab variance was higher in DK. Tuber size showed weaker G×E (r a = 0.82). Within mega-environments, genotype × environment components explained 16.8–26.9% of yield variance. Results indicate substantial re-ranking of breeding values; therefore, environment-specific prediction is recommended.

Altered Weddell Sea warm- and dense-water pathways in response to 21st-century climate change - Cara Nissen; Ralph Timmermann; Mathias van Caspel; Claudia Wekerle (Ocean Science, 2024)
The transport of water masses with ocean circulation is a key component of the global climate system. In this context, the Filchner Trough in the southern Weddell Sea is critical, as it is a hotspot for the cross-shelf-break exchange of Dense Shelf Water and Warm Deep Water. We present results from Lagrangian particle tracking experiments in a global-ocean–sea-ice model (FESOM-1.4) which includes ice-shelf cavities and has eddy-permitting resolution on the southern Weddell Sea continental shelf. With backward and forward experiments, we assess changes between a present-day and a future (SSP5-8.5) time slice in the origin of waters reaching the Filchner Ice Shelf front and the fate of waters leaving it. We show that particles reaching the ice-shelf front from the open ocean originate from 173 % greater depths by 2100 (median; 776 m as compared to 284 m for the present day), while waters leaving the cavity towards the open ocean end up at 35 % shallower depths (550 m as compared to 850 m for the present day). Pathways of water leaving the continental shelf increasingly occur in the upper ocean, while the on-shelf flow of waters that might reach the ice-shelf cavity, i.e., at deeper layers, becomes more important by 2100. Simultaneously, median transit times between the Filchner Ice Shelf front and the continental shelf break decrease (increase) by 6 (9.5) months in the backward (forward) experiments. In conclusion, our study demonstrates the sensitivity of regional circulation patterns in the southern Weddell Sea to ongoing climate change, with direct implications for ice-shelf basal melt rates and local ecosystems.